Comparing genetic differentiation and variation using ISSR and SCoT among Juniper plant markers in Saudi Arabia - Al-Yasi, Hatim M.; Al-Qthanin, Rahmah (Frontiers in Plant Science, 2024)
Juniperus, a genus of fragrant evergreen trees in the Cupressaceae family, encompasses up to 67 distinct species distributed globally. Among these, Juniperus procera, also known as the East African pencil cedar or African Juniper, stands out for its notable medicinal properties. Due to the well-recognized therapeutic benefits of Juniper species, assessing genetic diversity is essential for various breeding initiatives. Thus, in this work, six ISSR and six SCoT primers were utilized to evaluate the genetic diversity between 23 Juniper genotypes collected from different locations in Saudi Arabia. 29 out of 103 and 26 out of 105 amplified bands, respectively, were found to be polymorphic markers using the ISSR and SCoT studies. With the help of 120 genotype-specific markers, including 60 for ISSR and 60 for SCoT, several varieties of Juniper were discovered. In addition, the polymorphism information content (PIC) was computed to assess the effectiveness of the markers. The findings of this study highlight the importance of conserving the genetic diversity of Juniperus procera, as it holds immense potential for developing new medicinal products. Additionally, the results provide valuable insights into the genetic structure of Juniper populations in western Saudi Arabia, which can inform future conservation and management efforts. However, all of the techniques utilized to profile the genotypes of Juniper can be regarded as useful techniques for long-term fingerprinting and diagnostic markers.